Temporal Shift of Circadian-Mediated Gene Expression and Carbon Fixation Contributes to Biomass Heterosis in Maize Hybrids - Ko, Dae Kwan (PLoS Genet, 2016)
Heterosis has been widely used in agriculture, but the molecular mechanism for this remains largely elusive. In Arabidopsis hybrids and allopolyploids, increased photosynthetic and metabolic activities are linked to altered expression of circadian clock regulators, including CIRCADIAN CLOCK ASSOCIATED1 (CCA1). It is unknown whether a similar mechanism mediates heterosis in maize hybrids. Here we report that higher levels of carbon fixation and starch accumulation in the maize hybrids are associated with altered temporal gene expression. Two maize CCA1 homologs, ZmCCA1a and ZmCCA1b, are diurnally up-regulated in the hybrids. Expressing ZmCCA1 complements the cca1 mutant phenotype in Arabidopsis, and overexpressing ZmCCA1b disrupts circadian rhythms and biomass heterosis. Furthermore, overexpressing ZmCCA1b in maize reduced chlorophyll content and plant height. Reduced height stems from reduced node elongation but not total node number in both greenhouse and field conditions. Phenotypes are less severe in the field than in the greenhouse, suggesting that enhanced light and/or metabolic activities in the field can compensate for altered circadian regulation in growth vigor. Chromatin immunoprecipitation-sequencing (ChIP-seq) analysis reveals a temporal shift of ZmCCA1-binding targets to the early morning in the hybrids, suggesting that activation of morning-phased genes in the hybrids promotes photosynthesis and growth vigor. This temporal shift of ZmCCA1-binding targets correlated with nonadditive and additive gene expression in early and late stages of seedling development. These results could guide breeding better hybrid crops to meet the growing demand in food and bioenergy.